User's Research Interests Based Paper Recommendation System: A Deep Learning Approach - Bulut, Betul; Gundogan, Esra; Kaya, Buket; Alhajj, Reda; Kaya, Mehmet (Springer International Publishing Ag, 2020)
[Abstract Not Available]